ANALISIS KEMAMPUAN SHOOTING DALAM PERMAINAN SEPAK BOLA - M. Imran Hasanuddin (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2023)
This research is a descriptive study that aims to determine the ability of shooting kicks in the soccer game of SSB Ubhor athletes. Data collection uses the results of the football shooting ability test. The variable in this study is the ability to shoot kicks in soccer games for SSB Ubhor athletes. The population taken by 20 players in this study were SSB Ubhor players while determining the sample using the Total Sampling method. The results showed that the very good category had 2 athletes with a percentage of 10%, the good category had 5 athletes with a percentage of 25%, the medium category had 12 athletes with a percentage of 60%, the less category had 1 athlete with a percentage of 5% and the very poor category had 0 athletes with a percentage of 0%. Thus it can be concluded that the ability to shoot kicks in soccer games for SSB Ubhor athletes is in the "Medium" category with a percentage of 60%. Keywords: Shooting, Football.